Origin and Evolution of Protein Fold Designs Inferred from Phylogenomic Analysis of CATH Domain Structures in Proteomes - Bukhari, Syed Abbas; Caetano-Anollés, Gustavo (PLOS Computational Biology, 2013)
Author Summary Proteins are vital and central macromolecular players necessary for the functioning of the cell. The redundant and highly conserved structural makeup of proteins reflects their ability to act as genomic repositories of evolutionary history. These structures are fundamental subjects for the study of molecular evolution. Structural biologists have demonstrated the existence of a wide array of compact 3-dimensional fold structures, the protein domains. Their classification resulted in hierarchical taxonomies that describe protein fold space, most notable SCOP, CATH and FSSP. Studies have shown that certain types of protein shapes are more abundant than others and this uneven distribution implicates processes by which new shapes are discovered. Our evolutionary genomic research explores the evolution of protein domains at the deeper levels of classification. However, we have not embarked in a systematic study of the origin and evolution of general structural designs. These designs include topologies such as sandwiches, bundles, barrels, prisms, solenoids, and propellers. The appearance and diversification of general structural designs and their confirmation from published literature defines a unique chronology of structural innovation. The study also uncovers a recent trend of architectural sharing between Archaea and Eukarya and benchmarks the phylogenomic analysis of CATH domains with SCOP domains.